Community Participation of Community-Based Development in Malinau Regency North Kalimantan Province - Pandawa, Helmi; Achmad, Mansyur; Nurdin, Ismail; Sartika, Ika (Ridwan Institute, 2025)
The purpose of this study is to analyze community participation, supporting and inhibiting factors, and activities within the context of community-based development in Malinau Regency. Additionally, the study aims to identify and propose a more effective model of community participation in community-based development in Malinau Regency, North Kalimantan Province. The research is grounded in the participation theory proposed by Cohen and Uphoff (1977). A qualitative research method with a descriptive approach was employed. Data collection techniques included interviews, observation, and documentation. The findings indicate that community participation in community-based development activities in Malinau Regency is generally robust. Regarding inhibiting factors, the social aspect highlights the need to enhance residents’ capacity and awareness. In terms of culture, the study underscores the importance of maintaining values of gotong royong (mutual cooperation) and customary inclusiveness. Economically, issues such as poverty and the need for improved funding mechanisms persist. Politically, there is a call for consistent government commitment and the strengthening of two-way aspiration flow between stakeholders. Geographically, the conditions of the 3T (terdepan, terluar, tertinggal—frontier, outermost, and underdeveloped regions) continue to exert significant influence. The model of community participation in community-based development in Malinau Regency has proven effective due to its comprehensive and contextual approach. The three principal components—driving factors, participatory processes, and integrated outcomes/impacts—collectively establish a dynamic and people-centered development mechanism.